2012
DOI: 10.1002/jctb.3741
|View full text |Cite
|
Sign up to set email alerts
|

Electricity generation from seafood wastewater in a single‐ and dual‐chamber microbial fuel cell with CoTMPP oxygen‐reduction electrocatalyst

Abstract: BACKGROUND: To make the treatment of seafood wastewater more economical and sustainable, this study aims to examine electricity generation and simultaneous degradation of organic substances from seafood wastewater in single-chamber (SC) and dual-chamber (DC) microbial fuel cell (MFC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…A power density of 390 mW m − 2 was produced with an MFC used to treat seafood wastewater. Actually, no data was provided about the salinity, but it can be assumed to be high given the nature of the inoculum (Sun, 2012). More recently, 504 and 572 mW m − 2 were reached using MFCs inoculated with rice paddy-field soil working in NaCl up to 1.8 M (105 g L -1 ) (Miyahara et al, 2016;.…”
Section: Formation Of the Microbial Electrodes (Bioanodes And Or Biocathodes)mentioning
confidence: 99%
“…A power density of 390 mW m − 2 was produced with an MFC used to treat seafood wastewater. Actually, no data was provided about the salinity, but it can be assumed to be high given the nature of the inoculum (Sun, 2012). More recently, 504 and 572 mW m − 2 were reached using MFCs inoculated with rice paddy-field soil working in NaCl up to 1.8 M (105 g L -1 ) (Miyahara et al, 2016;.…”
Section: Formation Of the Microbial Electrodes (Bioanodes And Or Biocathodes)mentioning
confidence: 99%
“…The number of studies that evaluated the use of seafood wastewater in MFCs is limited, with only four studies identified in the literature, listed in Table 7. You et al (2010) The performance of small single-and two-chamber MFCs was compared using seafood wastewater with COD about 1000 mg/L (Sun, 2012). The study concluded that the single-chamber MFC produced higher power density (343.6-358.8 mW/m 2 ) than the two-chamber MFC (258.7-291.6 mW/ m 2 ).…”
Section: Seafood Industrymentioning
confidence: 99%
“…Pt-free transition metals oxides, such as Co, Fe and Mn-based electrocatalysts have gained increasing attention, owing to their durability, high performance, and relatively low-cost (Zhang et al 2014). For example, the introduction of metal element or metallic oxide, such as Fe (Anon n.d.), CoTMPP (Sun 2012), MnO X (R. Burkitt, T. Whiffen 2016), WC (Gong et al 2013), Pt-Ru/C (Yang et al 2016), Cobalt naphthalocyanine (CoNPc/C) (Rae et al 2011), Co-Al 2 O 3 -rGO (Papiya et al 2017), pristine stainless steel mesh/cobalt oxide (SSM/Co 3 O 4 ) (Gong et al 2014), Pt-Co alloy nanoparticles on graphene (Pt-Co/G) (Yan et al 2013) and Copper phthalocyanine (CuPc) were used as alternative electrocatalysts for enhancing the MFC performance (Ghasemi et al 2013).…”
Section: Introductionmentioning
confidence: 99%